2018
DOI: 10.4236/sgre.2018.912018
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Silicon Solar Cell Performance by Integration of an Electric Field Source in the Solar Cell or Solar Module System

Abstract: This manuscript is about a theoretical modelling of conversion efficiency improvement of a typical polycrystalline Si solar cell in 1D assumptions. The improvement is brought by the increase of the collection of the minority carriers charge in excess. This increase is the consequence of the influence of an electric field provided by the use of the open circuit photovoltage of another silicon solar cell. We assume that it is integrated two silicon solar cells to the system. The first solar cell provides the ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The PV conversion efficiency increase with the increase of the electromagnetic field. There is in this study a confirmation that an electromagnetic field mainly an electric field in low values assumptions can be used to improve the outputs of the polycrystalline silicon PV cell [25,27]. The doping level affecting the outputs of the PV cell, some individual efficiencies are represented in the next paragraph.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…The PV conversion efficiency increase with the increase of the electromagnetic field. There is in this study a confirmation that an electromagnetic field mainly an electric field in low values assumptions can be used to improve the outputs of the polycrystalline silicon PV cell [25,27]. The doping level affecting the outputs of the PV cell, some individual efficiencies are represented in the next paragraph.…”
Section: Resultsmentioning
confidence: 73%
“…It is the diffusion length depending to the magnetic field. The solution of this differential equation is given by δ 0 (x) the contribution in the density of minority carriers charge in excess of the PV cell in obscurity and δ I (x) the contribution of the PV cell under solar illumination [1,27]. Then the definitive solution is such as…”
Section: Excess Minoritary Carriers Chargementioning
confidence: 99%
“…The emitter contribution will be neglected and the base of the solar cell is assumed to be the real center of all the generation phenomenon's and the recombination phenomenon's. The integration of electrical field source in PV system is presented on Figure 1 [3]. The integration of the external electrical field is the addition of other solar cells to generate the open circuit voltage.…”
Section: Assessment Of the External Electrical Fieldmentioning
confidence: 99%
“…This study proposes that for the real operation condition of a domestical PV installation, it is better to use the external load resistance smaller than the real supported capability of the PV module. The integration of an additional electric field source in the solar cell has presented an improvement under monochromatic illumination [3] and under sun light illumination [4]. These studies have shown the possibility to increase the fill factor, the conversion efficiency and others outputs of a crystalline silicon solar cell by addition of an external electrical field.…”
Section: Introductionmentioning
confidence: 99%
“…The electromagnetic field from radio waves (9 kHz to 3000 GHz) [7,8] is composed of an electric field and a magnetic field which are perpendicular in the plane wave approach. The electric field causes individually the increase of the density of current produced by the PV cell [3,9]. However, the voltage provided by the PV cell decreases with the increase of the individual electric field mainly in the open circuit [3,9].…”
Section: Introductionmentioning
confidence: 99%